EMPLOYEE MENTAL HEALTH AND WORKPLACE PERFORMANCE IN THE NIGERIAN PUBLIC AND PRIVATE SECTORS (Journal of the Management Sciences, 2025)
Notwithstanding the recognised importance of employee performance for organisational success, the specific impact of employee mental health on sustained productivity, particularly in the context of Nigerian organisations, remains an under-explored area in existing literature. This study addresses this research gap by examining the connection between employees’ mental health and performance levels in specific organisations in Ibadan, Nigeria. The psychological, emotional, social, and occupational well-being of 400 employees from both public and private sectors was assessed using questionnaires that examined task, adaptive, and contextual aspects of performance. Findings from multivariate regression indicate that higher levels of mental health are associated with improved performance, accounting for 40.2% of task performance, 46.0% of adaptive performance, and 41.7% of contextual performance. These results underscore the critical importance of employee mental well-being for enhanced work outcomes and highlight the need for further research in this geographical and cultural context. The study implies that organisations should prioritise mental health initiatives, recommending policy updates to support wellness activities, foster safe work environments, and implement routine mental health checks.
Keywords: Mental Health; Task Performance; Adaptive performance; Contextual performance; Employee Performance